2019
DOI: 10.1186/s12935-019-0961-4
|View full text |Cite
|
Sign up to set email alerts
|

TUFT1 promotes metastasis and chemoresistance in triple negative breast cancer through the TUFT1/Rab5/Rac1 pathway

Abstract: Background Triple negative breast cancer (TNBC) is a breast cancer (BC) subtype that is characterized by its strong invasion and a high risk of metastasis. However, the specific mechanisms underlying these phenotypes are unclear. TUFT1 plays an important role in BC and impacts the proliferation and survival of BC cells. Recent studies have shown that TUFT1 mediates intracellular lysosome localization and vesicle transport by regulating Rab GTPase, but the relevance of this activity in TNBC is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, in lung cancer cells, TUFT1 seems to enhance tumorigenesis through mTORC1 signaling pathway [ 39 ]. In addition, in breast cancer, TUFT1 promotes metastasis and chemoresistance through Rab5/Rac1 pathway [ 21 ]. These findings indicate that TUFT1 exerts oncogenic functions in different cancers, but the underlying mechanisms may differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in lung cancer cells, TUFT1 seems to enhance tumorigenesis through mTORC1 signaling pathway [ 39 ]. In addition, in breast cancer, TUFT1 promotes metastasis and chemoresistance through Rab5/Rac1 pathway [ 21 ]. These findings indicate that TUFT1 exerts oncogenic functions in different cancers, but the underlying mechanisms may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TUFT1 expression is reported to be elevated in several types of cancers including hepatocellular carcinoma (HCC), breast cancer, thyroid carcinoma and osteosarcoma [18][19][20]. Increased expression of TUFT1 can promote the growth and metastasis of cancer cells through distinctive pathways in different cancers [20,21]. Moreover, TUFT1 expression is associated with unfavorable clinical outcomes and poor prognosis of HCC [20].…”
Section: Introductionmentioning
confidence: 99%
“…TUFT1 has been demonstrated to be a key regulator in various cancers including breast cancer, pancreatic carcinoma and lung adenocarcinoma. 23,37,38 Our results indicated that the ATF2/miR-548p-mediated suppressive effects in HCC were dependent on controlling TUFT1 expression. Combined with other results and literatures, we speculated that ATF2/miR-548p/TUFT1 axis regulates HCC progression.…”
Section: Discussionmentioning
confidence: 65%
“…CDKN2A was found to be inactivated in EC and its hypermethylation was correlated with an increased risk of EC [ 26 , 27 ]. The HER2 (ERBB2) gene is amplified in 17–33% of carcinosarcoma, uterine serous carcinoma, and a subset of high-grade endometrioid endometrial tumors [ 28 , 29 ]. However, for the remaining genes, their functions have not been revealed in EC.…”
Section: Discussionmentioning
confidence: 99%